The figure-of-8 aortic valve suturing technique optimizes the effective orifice area of a small aortic annulus—an ex vivo study. (5th April 2022) - Saisho, Hiroyuki; Kuhlmann, Carina; Scharfschwerdt, Michael; Jeganathan, Reuben; Sadat, Najla; Schaller, Tim; Aboud, Anas; Ensminger, Stephan; Fujita, Buntaro
Abstract: OBJECTIVES: Surgical aortic valve replacement (SAVR) in small annuli carries an elevated risk for the patient–prosthesis mismatch. In this study, we systematically investigated the influence of different implantation techniques including annular enlargement (AE) on the functional result after SAVR in small annuli using a standardized ex vivo model. METHODS: SAVR using the PERIMOUNT Magna Ease ® (PME) 21 mm was performed in small porcine aortic roots using 4 implantation techniques: non-everting pledgeted (NE) suture, single interrupted (SI) suture, continuous suture (CS), figure-of-8 (F8) suture, as well as the PME 23 mm after AE using the Nunez method and the NE suture technique (PME23 AE). The effective orifice area (EOA), mean pressure gradient and leakage volume were evaluated using a mock circulation loop in accordance with ISO regulations. RESULTS: Experiments were conducted on 31 porcine aortic roots. PME21 using F8 and PME23 after AE achieved a significantly larger EOA than using NE. PME23 after AE showed a larger EOA than the PME21 using any suture technique, except the F8 [for stroke volume of 74 ml: PME21 NE: 1.68 (1.63–1.72) cm 2, PME21 SI: 1.76 (1.68–1.81) cm 2 ( P = 0.17), PME21 CS: 1.76 (1.65–1.79) cm 2 ( P = 0.14), PME21 F8: 1.81 (1.70–1.85) cm 2 ( P = 0.005); PME23 AE: 1.83 (1.73–1.92) cm 2 ( P < 0.001)]. SI and CS did not result in larger EOA compared with the NE technique. PME21 using SI had a significantly larger leakage volume than using NE and there was no significant difference between other techniques [for stroke volume of 74 ml: PME21 NE: 3.51 (1.85–4.53) ml/stroke, PME21 SI: 6.00 (4.02–7.06) ml/stroke ( P < 0.001), PME21 CS: 4.04 (3.60–4.49) ml/stroke ( P = 0.10), PME21 F8: 3.16 (1.99–3.62) ml/stroke ( P = 0.74), PME23 NE: 2.89 (2.45–4.72) ml/stroke ( P = 0.51)]. CONCLUSIONS: The F8 technique with the PME21 achieved a similar EOA as the 1 size larger PME23 using NE after AE. These results suggest that the F8 technique may be an effective surgical modification to improve the haemodynamic result in a small annulus without additional AE. Abstract : Surgical aortic valve replacement (SAVR) is the recommended option for the treatment of aortic stenosis in patients at lower surgical risk, as well as patients suffering from aortic regurgitation if valve-sparing surgery is not possible [1, 2].